The effect of the strategy to nominate ideas on divided and selective attention and perform some volleyball skills - Fadya Abdul Hussein Kadhim; Alyaa Hussein Farhan; Tahseen Husnl Tahseen; Suhad Qassem Saeed Al-Mousawi; Haider Radhi Raheem (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Attention is a fundamental cognitive function in sports, particularly in volleyball, where players must process multiple stimuli and make rapid decisions. Effective attentional control can enhance an athlete’s ability to react to dynamic game situations. The nomination of ideas strategy. Objective: This study aims to examine the effectiveness of the nomination of ideas strategy in enhancing divided and selective attention and its subsequent impact on volleyball skill performance. Methodology: A controlled experimental design was employed, involving volleyball players divided into an experimental group and a control group. The experimental group integrated the nomination of ideas strategy into their training sessions, while the control group followed traditional training methods. Pre- and post-tests were conducted to assess selective attention, divided attention, and volleyball skill performance, ensuring a comprehensive evaluation of cognitive and motor improvements.